Public support for innovation, intangible investment and productivity growth in the UK market sector - Jonathan Haskel; Gavin Wallis (Institute for the Study of Labor (IZA), 2010)
Pressure on public finances has increased scrutiny of public support for innovation. We examine two particular issues. First, there have been many recent calls for the (relatively new) UK R&D subsidy to be extended to other research activities, such as software. Second, argument still rages about the efficacy of direct public spending on R&D via spending on academic research councils, universities, and government undertaken work on civil and military R&D. To evaluate these questions we use data on market sector productivity, R&D and non-R&D intangible assets, and public sector R&D spending. We look for evidence of market sector spillovers from intangible investment and from public R&D. We find (a) no evidence of spillover effects from intangible investment at the market sector level, including from R&D, (b) strong evidence of market sector spillovers from public R&D spend on research councils, and (c) no evidence of market sector spillovers from public spending on civil or defence R&D. Our findings tentatively suggest that for maximum market sector productivity impact government innovation policy should focus on direct spending on research councils.
Keywords: O47; E22; 330; Intangible assets; productivity; R&D; spillovers; Forschungssubvention; Forschungs- und Technologiepolitik; Innovationspolitik; Immaterielles Anlagevermögen; Investition; Produktivität; Industrielle Forschung; Öffentliche Forschung; Spillover-Effekt; Großbritannien